A report and commentary on 5 cases from Wards 28 and 29 of the Royal Infirmary: written for the Wightman Prize in Clinical Medicine - Henderson, R. J. (The University of Edinburgh, 1933)
A case of primary lung cancer.

A case of acute haemolytic anaemia

A case of auricular flutter

Two cases, myelo gen ous leukaemia and Lymphadenoma: illustrating the use of X-ray therapy